GUIDED QUESTIONS TECHNIQUE FOR TEACHING WRITING SKILL OF DESCRIPTIVE TEXT - Indrasari, Nunun; Julita, Riana (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The objective of the research was to find out whether there was a significant influence of using Guided Questions technique towards students’ writing skill of descriptive text at the first semester of the eighth grade students of SMP Perintis 2 Bandar Lampung in the academic year of 2017/2018. The methodology in this research was quasi experimental design with the treatments held in 3 meetings, 2x40 minutes for each. The population of this research was the eighth grade students of SMP Perintis 2 Bandar Lampung. The sample taken was two classes, VIII B and VIII C which consisted of 37 students respectively by using Cluster Random Sampling. In collecting the data, the writer used the test instrument in writing descriptive text. Pre-test and post-test design was used. From the data analysis, it was found that the result of T-test was 2.155. This result then was consulted to the score of t-critical in this case 0.05 was 1.994. From the analysis, the score of t_observed was higher than t_critical (0.05). In conclusion, Ha was accepted and Ho was rejected. In other words, there was a significant influence of guided questions towards students’ writing descriptive text of the eighth grade students of SMP Perintis 2 Bandar Lampung in the academic year of 2017/2018.Key Words: Writing, Descriptive Text, Guided Questions, Quasi Experimental Design